Multimedia educativa de apoyo al proceso de enseñanza aprendizaje para el área de ciencias naturales dirigido a los estudiantes de octavo año de educación básica del colegio nacional nocturno Catamayo” de la provincia de Loja, cantón Catamayo, periodo 2011 – 2012 - Sánchez Azuero, Betty Elizabeth (2014)
This research was conducted at the "Night Catamayo" National College for the period 2011 - 2012 with the theme: "MULTIMEDIA EDUCATIONAL SUPPORT FOR LEARNING PROCESS OF TEACHING NATURAL SCIENCES AREA TARGETS EIGHTH YEAR STUDENTS OF BASIC EDUCATION NATIONAL COLLEGE NIGHT CATAMAYO "Loja PROVINCE, CATAMAYO CANTON, PERIOD 2011-2012. This research work proposes the general objective: Develop an educational multimedia support teaching and learning process for the area of Natural Sciences students led Eighth Year of Basic Education "Night Catamayo" National College, in the province of Loja, Catamayo Canton, 2011-2012. The methods used for this research were: scientific, inductive, deductive, analytical, descriptive method and the statistical model that helped to properly route each of the phases of the research; techniques and tools for data collection used was the same as the survey was used to collect information at the beginning of software development as well as validation of the same, both students and teachers of the institution. In addition to direct observation of the research process beginning at school, "National Catamayo Night" was performed. In the results obtained from the surveys of both teachers and students, it was determined that 100% of the contents correspond to the curriculum, 100% of teachers believe that students would feel motivated to use the media to learn science natural, and 100% of students report that there is no difficulty when using multimedia. The teacher states that are willing to use educational software to support the teaching and learning process in the course of Natural Science as if through interactive interface to motivate students and bring more attention to their classes. Finally, conclusions and recommendations that follow from the interpretation, analysis and inference based on the data obtained and its comparison with the theoretical and conceptual references, in which it is concluded that educational software should be used by students are set the 8th Year of Basic Education.